Hey shirley,

Following pls find my worked solution:

<after>

A : C

3 : 2

using <work backwards> method and since these 3u left of A are (1/2) of what A had originally, we have ...

<before>

A : C

6 : 2

Givent that A - C = 360, we have ...

6u - 2u --> 360

4u --> 360

1u --> 90

(a)

A (left) = 3u --> 3 × 90 = **$270**

(b)

<before>

A : C

3 : 2

<before> total = A + C = 5u --> 5 × 90 = $450

<after>

A : C

8 : 7

Apply <Unchanged Total> concept, we have ...

<after> A + C = 8p + 7p = 15p --> 450

1p --> 30

A (after) = 8p --> 8 × 30 = 240

A gave C = A (before) - A (after)

= 270 - 240 = **$30**

==============================

Trust this helps.

Do let me know again if this is different from your answerkey or if there's further clarification.

Cheers,

Edward